Pendampingan Program Pengembangan Klaster Bawang Merah Di Kabupaten Bojonegoro - Joko Hadi Purnomo; Niswatin Nurul Hidayati (IAI Darussalam, 2021)
The purpose of assisting the development of onion clusters in Bojonegoro Regency is to improve the quality of sustainable production and expand the marketing reach of processed shallot products. The method used is Participatory Action Research (PAR). The results of the assistance carried out are that the quality of the products produced by the Mekar Sari farmer group is able to match the fried onion products of other competitors in the local and interlocal markets, the market opportunities for fried onions and chili sauce are still very large both in the local market and in other areas. there is a market mapping of fried onions and chili sauce to distribute the product, as well as, there needs to be a commitment from the fried onion production team where buyers have started to arrive.